Review of the Paratydeidae (Acari: Prostigmata), with description of three new species - Khaustov, Alexander A. (Zootaxa, 2017)
The family Paratydeidae is reviewed. The genera Paratydeus, Sacotydeus and Walytydeus are considered as junior synonyms of Scolotydaeus, but Neotydeus is confirmed as a distinct genus. Five species are redescribed: Neotydeus ardisanneae Baker, 1950, Scolotydaeus alexanderi (Baker, 1949) comb. nov. (from Paratydeus) , S. lootsi (Theron et al., 1969) comb. nov. (from Sacotydeus), S. tauricus (Kuznetsov, 1973) comb. nov. (from Walytydeus), Tanytydeus simplex (Delfinado and Baker, 1974) comb. nov. (from Scolotydaeus). Tanytydeus cf. aegyptiacus (Soliman, 1974) is described from Crimea, and three new species are described: Scolotydaeus uralensis sp. nov. from Russia, Tanytydeus cubanus sp. nov. from Cuba, and T. kethleyi sp. nov. from the USA. All developmental stages are described for the first time for Scolotydaeus and Tanytydeus. Keys to life stages, genera and species of Paratydeidae are provided.